Functional G-Protein-Coupled Receptor (GPCR) Synthesis: The Pharmacological Analysis of Human Histamine H1 Receptor (HRH1) Synthesized by a Wheat Germ Cell-Free Protein Synthesis System Combined with Asolectin Glycerosomes - Suzuki, Yasuyuki; Ogasawara, Tomio; Tanaka, Yuki; Takeda, Hiroyuki; Sawasaki, Tatsuya; Mogi, Masaki; Liu, Shuang; Maeyama, Kazutaka (Frontiers in Pharmacology, 2018)
G-protein-coupled receptors (GPCRs) are membrane proteins distributed on the cell surface, and they may be potential drug targets. However, synthesizing GPCRs in vitro can be challenging. Recently, some cell-free protein synthesis systems have been shown to produce a large amount of membrane protein combined with chemical chaperones that include liposomes and glycerol. Liposomes containing high concentrations of glycerol are known as glycerosomes, which are used in new drug delivery systems. Glycerosomes have greater morphological stability than liposomes. Proteoglycerosomes are defined as glycerosomes that contain membrane proteins. Human histamine H1 receptor (HRH1) is one of the most studied GPCRs. In this study, we synthesized wild-type HRH1 (WT-HRH1) proteoglycerosomes and D107A-HRH1, (in which Asp107 was replaced by Ala) in a wheat germ cell-free protein synthesis system combined with asolectin glycerosomes. The mutant HRH1 has been reported to have low affinity for the H1 antagonist. In this study, the amount of synthesized WT-HRH1 in one synthesis reaction was 434 ± 66.6 µg (7.75 ± 1.19 × 103 pmol). The specific binding of [3H]pyrilamine to the WT-HRH1 proteoglycerosomes became saturated as the concentration of the radioligand increased. The dissociation constant (Kd) and maximum density (Bmax) of the synthesized WT-HRH1 were 9.76 ± 1.25 nM and 21.4 ± 0.936 pmol/mg protein, respectively. However, specific binding to D107A-HRH1 was reduced compared with WT-HRH1 and the binding did not become saturated. The findings of this study highlight that HRH1 synthesized using a wheat germ cell-free protein synthesis system combined with glycerosomes has the ability to bind to H1 antagonists.